Behavior of 175 kg/cm² concrete in channels at 2800 - 3500 m above sea level (Aporte Santiaguino, 2025)
The objective of this research was to analyze the impact of altitudinal variation on the behavior of concrete of 175 kg/cm² used in channels located between 2800 and 3500 m a.s.l., through the use of a plasticizer additive. The study was carried out in the province of Huaylas during September 2024, under an experimental methodology with a quantitative approach and experimental design. The study population consisted of channel sections located within the established altitudinal range. The research is framed in the need to contribute to the development of resilient infrastructures, promote sustainable industrialization and foster innovation, considering that economic growth, social development and climate action depend to a large extent on efficient investments in infrastructure. The results showed that the incorporation of the Super Plast Chema plasticizer allows obtaining a concrete with greater conservation of its initial conditions of workability, as well as an increase in the speed of strength gain, reaching and exceeding the specified strength before 28 days of curing.
Keywords: additive; variation